Islam and Arat Sabulungan in Mentawai - Delfi, Maskota (Al-Jamiah Research Centre, 2013)
The remoteness of the Mentawai Islands has contributed to an almost autonomous development, unaided by mainland Sumatra. As a result of a well endowed environment and supported by staple local foods such as sago, taro and bananas, as well as an abundance of wildlife including wild boars, a finely tuned self-sufficiency was realised. In this space the management and distribution of food, including animal protein, is an important aspect of the culture of Arat Sabulungan. As the result of the compulsory state sanctioned religions program introduced in 1954, some Mentawaians have converted to Islam or Catholicism as their formal religious identity. However, a remarkable adaptation occured in which the layers of Mentawai identity were not lost in the adaption to the Islamic faith. Islam with its teachings, and other formal religions, are considered as the sasareu (outsiders). The prohibition of consuming boar as part of islamic rules is a sasareu rules that contradict to Mentawaian Arat.[Kepulauan Mentawai yang terisolasi telah berkembang secara mandiri tanpa bantuan dari pulau induknya, Sumatra. Lingkungan yang subur dan mendukung ketersediaan sumber makanan pokok lokal seperti sagu, talas, dan pisang serta berlimpahnya satwa liar, termasuk babi hutan, telah mendorong terciptanya swasembada pangan. Manajemen dan distribusi makanan merupakan aspek penting dalam jalinan budaya dan sistem kepercayaan local, Arat Sabulungan. Sebagai hasil dari kebijakan pemerintah untuk menerapkan agama resmi bagi orang Mentawai pada tahun 1954, orang Mentawai kemudian masuk Islam atau Katolik. Namun demikian, adaptasi yang luar biasa juga terjadi, sehingga lapisan-lapisan identitas Mentawai tidak hilang dalam adaptasinya dengan keyakinan Islam. Islam dengan ajaran-ajarannya, juga agama-agama dunia lainnya, dipandang sebagai ajaran asing. Larangan mengkonsumsi daging babi sebagai bagian dari ajaran Islam, misalnya, dipandang sebagai ajaran asing yang bertentangan dengan Arat Mentawai.]Â